Foliar dust as a reliable environmental monitor of heavy metal pollution in comparison to plant leaves and soil in urban areas. (January 2022) - Li, Changchao; Du, Daolin; Gan, Yandong; Ji, Shuping; Wang, Lifei; Chang, Mengjie; Liu, Jian
Abstract: Pollution of atmospheric particulate matter carrying heavy metals has posed a great threat to various ecosystem compartments. Here, a total of 540 samples from four ecosystem compartments (plant leaves, foliar dust, surface soil, and subsoil) were collected in urban soil-plant systems to characterize the heavy metal concentration and composition of foliar dust, to verify the suitability of foliar dust as an environmental monitor, and to explore the importance of foliar dust in shaping the heavy metal composition in plant leaves. We found that the concentrations of all detected elements (lead, zinc, copper, chromium, nickel, and manganese) in foliar dust were the highest among the four ecosystem compartments. The mass of element per unit leaf area, considering both the dust retention amount and the heavy metal concentration of foliar dust, had significant positive correlations with the degree of heavy metal pollution in soil. Foliar dust could reflect ambient elemental composition most reliably among the four ecosystem compartments. The above findings show that foliar dust is more suitable for environmental monitoring than soil and plant materials in urban areas. In addition, the elemental composition of plant leaves differed significantly with different soil-plant systems although species identity dominated the leaf elemental composition. The variation partitioning model and the partial correlation analysis confirm that foliar dust plays a more important role in shaping the elemental composition of plant leaves than soil. This study provides a new way for environmental pollution monitoring and contributes to a comprehensive understanding of atmospheric particulate matter. Graphical abstract: Image 1 Highlights: Foliar dust has higher concentrations of heavy metals than soil and plant leaves. Foliar dust reflects ambient elemental composition better than soil and leaves. The mass of element per unit leaf area is suitable to evaluate environmental quality. Foliar dust has a greater effect on the plant leaf elemental composition than soil.